Training Civics Teachers in the Utilization of AI-Based Interactive Simulations to Enhance Students’ Civic Literacy and Ethical Decision-Making - Melati, Prima; Robby Al-Fathy, Rifqi Fadli; Hayat, Rizky Saeful; Rahmawati, Sri Devi; Damayanti, Syfa Kaila; Cantika, Tira; Martiani, Ulpa Dwi (Indonesian Journal of Community Empowerment (IJCE), 2025)
This community service program aims to enhance the competence of Civic Education (PKn) teachers in utilizing AI-based interactive simulations to foster students’ civic literacy and ethical decision-making skills. The program was implemented through two main stages: (1) the introduction of Artificial Intelligence concepts and their relevance in education, and (2) practical training on integrating AI-based interactive simulations into classroom learning. The results demonstrate that the training improved teachers’ digital literacy, strengthened their pedagogical capacity, and encouraged the adoption of innovative learning media. Consequently, students gained greater opportunities to engage in critical thinking, understand their rights and responsibilities as citizens, and practice ethical decision-making in real-life contexts. This program highlights the strategic role of teacher training in supporting the integration of technology into Civic Education, while also offering implications for broader educational practices in the digital era.